2019
DOI: 10.22207/jpam.13.3.48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eosinophilic Cationic Protein and Some Immunological Markers in Patients Infected with Scabies

Abstract: The current study is trying to identify some effects of scabies on some vital indicators such as (ECP, IgE, MCP-1 and IL-17). The results showed that levels of ECP has significant increase (P<0.05 (9569.3 ±256.10 pg /ml), (9872.9± 260.50) respectively in comparison with the control group (7665.2 ± 385.72 pg /ml), (7834.1± 251.43 pg /ml) respectively, The result proved that there was the significant increase (P (9721.1 ±181.15 pg /ml), (7749.7± 226.75) respectively in concentration of (ECP) in patients with S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…As compared to those in the control group, patients with T.vaginalis infections had significantly lower copper levels. Copper, zinc, and magnesium are crucial for growth and development in growing children and play a crucial part in the metabolism and physiology of the human body, so these results may be caused by the virulence factors of this parasite (16,17). These results are in line with those of Uwah et al (18), who found that patients with parasite infections had lower serum levels of zinc, copper, and magnesium than did the control group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As compared to those in the control group, patients with T.vaginalis infections had significantly lower copper levels. Copper, zinc, and magnesium are crucial for growth and development in growing children and play a crucial part in the metabolism and physiology of the human body, so these results may be caused by the virulence factors of this parasite (16,17). These results are in line with those of Uwah et al (18), who found that patients with parasite infections had lower serum levels of zinc, copper, and magnesium than did the control group.…”
Section: Discussionsupporting
confidence: 83%
“…In this investigation, samples were compared using the T-test with Graph-Pad Prism version 10 software. A p-value of 0.05 or less is regarded as statistically significant (14,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Scabies commonly occurs in elderly patients, and classic scabies can resemble Th2 immunity‐related dermatological diseases, such as atopic dermatitis (AD) and prurigo nodularis (PN) 1 . Elevated serum immunoglobulin E (IgE) levels have been reported during scabies infections, which reduced after the scabies was treated 2,3,4 . Here, we report, for the first time, a case of pruritic scabies, involving elevated serum thymus and activation‐regulated chemokine (TARC) levels, which decreased after the scabies was treated.…”
Section: Figurementioning
confidence: 94%
“…1 Elevated serum immunoglobulin E (IgE) levels have been reported during scabies infections, which reduced after the scabies was treated. 2,3,4 Here, we report, for the first time, a case of pruritic scabies, involving elevated serum thymus and activation-regulated chemokine (TARC) levels, which decreased after the scabies was treated.…”
Section: Serum Thymus and Activationregulated Chemokine Levels Beforementioning
confidence: 97%
“…A statistical package (Statistical Package for Social Sciences, version 20, IBM, and Armonk, New York) was used to collect and analyze the data [17,18]. A mean and standard deviation were used to summarize the quantitative data; numbers and percentages were used to summarize qualitative data, correlation was used to determine correlations, and a P-value<0.05 was considered significant [19,20].…”
Section: Statically Analysismentioning
confidence: 99%